The use of a functional approach as surrogate of Collembola species richness in European perennial crops and forests - Reis, Filipa S. (2018)
Collembolans are known indicators of soil disturbance, used in several soil biodiversity monitoring programmes. As for other groups of soil microarthropods, taxonomic determination of Collembola species requires a huge effort and expert knowledge. In this study, we evaluated whether identification of Collembola species to the morphotype level, using an eco-morphological index which classifies individuals based on their adaptation to the soil, can be used as a surrogate of species richness in extensive monitoring schemes. The same evaluation was performed for higher taxa surrogates, using taxonomic categories at the genus and family levels. Additionally, sampling effort for perennial crops and forest systems was determined. Species data were collected from 35 sites sampled within different projects with the same number of samples (16 per site). Results showed that, on average, 8-12 samples are enough to have a good estimate of species richness for this type of systems, averaging 80-90%, but varying considerably with site habitat heterogeneity and local Collembola species pool. GLM models (using species richness as response variable) fitted for family, genus or morphotype levels (explanatory variables) were all significant (p < 0.05) but only the latter two had a pseudo R 2 higher than 0.75. This indicates that when a rapid, cost-effective assessment of Collembola richness in different sites is required, this eco-morphological trait approach, as well as the determination to the genus level, could be used.